ANALISIS KUALITAS UDARA AMBIEN AKIBAT LALU LINTAS KENDARAAN BERMOTOR DI KAWASAN COYUDAN, SURAKARTA - Dyah Ratri Nurmaningsih (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2018)
Surakarta is a city that has very rapid growth in many sectors such as in industry, services, settlements, education, trade and transportation. The main trading activity center or CBD (Central Bussiness Distric) in Surakarta City, is located in the Coyudan Surakarta shopping area, which makes this area becomes a strategic and congested traffic access point. This condition cause a high volume of traffic in the area. Motorized vehicle’s traffic activity on its road segment has a negative impact to surrounding area along the road segment as an air pollution. The more rapid transportation activities, especially motorized vehicles, are the main sources of air pollution in urban areas. The research method for this study is a survey method (for selecting research points) and approach analysis methods (using an empirical formula). The results of this study indicate that the parameters of exhaust emissions which include CO, HC, NO, and PM still meet the permitted air quality standards. However, it is expected that all people keep paying attention to both environmental conditions and the use of transportation facilities, as well as good traffic conditions, so that the problem of exhaust emissions due to traffic will not occur. Keywords: traffic, CBD and exhaust emissions.